The strangers. Chapter 1 [videorecording (DVD)] - Cohen, Alan R.; Freedland, Alan; Bertino, Bryan; Petsch, Madelaine, 1994-; Gutierrez, Froy, 1998-; Basso, Gabriel, 1994-; Horvath, Ema; Bruccoleri, Ella (Lionsgate, 2024)
After their car breaks down in an eerie small town, a young couple is forced to spend the night in a remote cabin. Panic ensues as they are terrorized by three masked strangers who strike with no mercy and seemingly no motive.